Block median filters - Kasparis, Takis; Memon, Qurban A. (My University, 1995)
Rank and median filters (MFs) have become one of the standard techniques for suppressing noise of impulsive nature. A limitation of these filters is the high computational cost when implemented on general purpose computers. Several fast algorithms have been developed for specific types of signals. An alternative is computationally more efficient filters with MF-like performance. One proposed filter in this category with selectable trade-off between reduction of computation and MF-like performance is the block median filter (BMF). The BMF produces a median block at each window position, thus effectively reducing the total window steps and the computation. In this paper some statistical properties of the BMF and comparisons with the MF are presented. It is shown that for large window sized, the statistical properties of the BMF approach those of the MF.
Keywords: Algorithms; Statistical methods; Cost effectiveness; Filters and filtration